2012
DOI: 10.1111/j.1349-7006.2012.02310.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐thermal DNA damage of cancer cells using near‐infrared irradiation

Abstract: Previously, we reported that near-infrared irradiation that simulates solar near-infrared irradiation with pre-and parallel-irradiational cooling can non-thermally induce cytocidal effects in cancer cells. To explore these effects, we assessed cell viability, DNA damage response pathways, and the percentage of mitotic cancer cells after near-infrared treatment. Further, we evaluated the anti-cancer effects of near-infrared irradiation compared with doxorubicin in xenografts in nude mice by measuring tumor volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 32 publications
(47 reference statements)
0
33
0
Order By: Relevance
“…Therefore, various devices have been introduced to stimulate collagen production. I previously reported that near-infrared can penetrate deep into human tissue, achieve skin tightening and muscle thinning, and nonthermally induce various responses in the skin and subcutaneous tissues [4][5][6][7][8][9][10][11]. In addition, I previously reported that near-infrared or radiofrequency (RF) treatments stimulate collagen and elastin production while safely and effectively promoting long-lasting skin tightening results that decrease wrinkles and laxity [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, various devices have been introduced to stimulate collagen production. I previously reported that near-infrared can penetrate deep into human tissue, achieve skin tightening and muscle thinning, and nonthermally induce various responses in the skin and subcutaneous tissues [4][5][6][7][8][9][10][11]. In addition, I previously reported that near-infrared or radiofrequency (RF) treatments stimulate collagen and elastin production while safely and effectively promoting long-lasting skin tightening results that decrease wrinkles and laxity [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…These reports made it clear that infrared radiation could affect internal organs and hence the reproductive tissues were also at risk. Tanaka et al (2012) further demonstrated that the cell viability of cultured lung adenocarcinoma cells was significantly decreased after near-infrared irradiation at 20 J/cm, with increase in Apoptotic cells. In addition these researchers have shown that nearinfrared and doxorubicin inhibited the tumor growth of melanoma cells suggesting that nearinfrared irradiation can non-thermally induce cytocidal effects in cancer cells as a result of activation of the DNA damage response pathway.…”
Section: Adverse Effects -Caveats From Literaturementioning
confidence: 94%
“…We previously reported that near-infrared can penetrate deep into human tissue, achieve skin tightening [2][3][4] and muscle thinning [5,6], and non-thermally induce various responses in the skin and subcutaneous tissues [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%